1987
DOI: 10.2135/cropsci1987.0011183x002700040026x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drought on Water Relations of Developing Maize Kernels1

Abstract: Although considerable information exists concerning the effect of drought on the water relations of maize (Zea mays L.) leaves, little has been published about the water relations of maize grain, or on how the process of grain filling is affected by a limited water supply. We had previously observed that the maize plant sustained normal rates of kernel growth for long periods in spite of severe water deficit during grain filling. The objective of this study was to investigate the nature of that response. Plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 0 publications
5
22
0
1
Order By: Relevance
“…Maintenance of a favorable water status within the seed may be an important prerequisite for conserving seed growth rate under adverse environmental conditions. Observations similar to those reported here have been made in maize, wheat, barley, and rice (2,7,19,22). The breadth of these observations suggests that the apparent independence of seed water status from that of the maternal tissues may be a phenomenon common to all seeds.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Maintenance of a favorable water status within the seed may be an important prerequisite for conserving seed growth rate under adverse environmental conditions. Observations similar to those reported here have been made in maize, wheat, barley, and rice (2,7,19,22). The breadth of these observations suggests that the apparent independence of seed water status from that of the maternal tissues may be a phenomenon common to all seeds.…”
Section: Resultssupporting
confidence: 83%
“…They also suggested that the developing seed of soybean might be buffered from water deficits experienced by maternal plant tissues as has been observed for caryopses of several grass species (2,7,19,22). To investigate this possibility, we measured the *', of leaf, pericarp, and seed tissues of soybean plants from which water was withheld during the period of rapid seed growth.…”
Section: Resultsmentioning
confidence: 97%
“…In developing bean (Phaseolus vulgaris L.) seeds, water and osmotic potentials ofembryo tissues changed independently of maternal tissues (25). Maize (Zea mays L.) kernel water relations were unaffected by imposed water deficits that caused significant declines in water and osmotic potentials of leaves (12,22 and osmotic potentials declined during late growth and maturation in both wheat (1) and maize (21).Increasingly, evidence is pointing to the regulation of solute availability to developing embryos and endosperm by water relations of the embryo itself and the surrounding medium (2, 13, 18, 19, 23) (and others). Although solute unloading rates from seed coats varied considerably with the osmolality of the receiving medium in P. vulgaris L. (13), faba bean (Vicia faba L.), and pea (Pisum sativum L.) (23), sucrose unloading rates from attached soybean seed coats were reduced only at trap solution concentrations over 500 mM (18).…”
mentioning
confidence: 99%
“…In developing bean (Phaseolus vulgaris L.) seeds, water and osmotic potentials ofembryo tissues changed independently of maternal tissues (25). Maize (Zea mays L.) kernel water relations were unaffected by imposed water deficits that caused significant declines in water and osmotic potentials of leaves (12,22). Similarly, a lack of response of grain water relations to imposed severe water deficits was observed in wheat (Triticum aestivum L.) (1).…”
mentioning
confidence: 99%
“…Other work of Ouattar et al, (1987) concluded that sifting period for drought stress tolerance could extend until the grain development phase. (Table 5).…”
Section: Wwwintechopencommentioning
confidence: 99%